The impact of rural electrification and institutional quality on agricultural output : a case of Sub-Saharan Africa - Amuakwa-Mensah, Salome (SLU/Dept. of Economics, 2019)
Agriculture is the means of livelihood for most rural communities in Sub-Saharan Africa. In order for small-scale farmers to meet the basic needs of their families and semi-large-scale farming for trading purposes, rural farmers seek to expand their output. To this end, the kind of input employed in the crop production process is very important. In terms of labour, most rural farmers employ their children or other family members and or members of the community where they use traditional farming tools. The use of energy and for that matter, electricity is very little. What happens when rural farmers have access to electricity? What happens if their homes and farms had a constant supply of electricity? Would the farmers spend more time on the farm knowing that they could increase their output and finish household tasks later in the evening when it gets dark because they have access to electricity? The purpose of this thesis is to test the impact of rural electrification on agricultural output. More precisely, I focus on rural household access to electricity on a macro level. I also try to draw a link between a country’s institutional quality and the impact of electrification. I make use of data drawn from the Food and Agriculture Organization of the United Nations, World Bank Development Indicators Aklin, S. P., & Urpelainen (2018) and the World Bank Climate Change Knowledge Portal, using date from 1990 to 2016. To do this, I employ a simple Cobb-Douglas production function approach where agricultural output is a function of labour, capital, electrification and other inputs such as rainfall, temperature and land. I later introduce a variable which measures the quality of institution for a country. The study concludes that rural electrification does have a positive effect on agricultural output; the interaction between electrification and institutions has a significant positive effect on agricultural output; and the efficiencies of labour and land also have a positive effect on agricultural output. For this reason, I suggest that governments and policymakers should focus on providing electricity to their rural communities to increase yield in agriculture.